Financial Literacy and Perceived Ease of Use on Interest in Using E-Wallet (Case Study of Employees at PT Tanjung Timberindo Industry) - Jenny Novita Sari; Susan Grace Veranita Nainggolan; Tri Wulandari (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2023)
This study aims to determine the impact of financial literacy and perceived ease of use on interest in using E-Wallet as a means of payment used by employees of PT Tanjung Timberindo Industry. This study uses quantitative research data methods with primary data sources that use questionnaires as data collection instruments. The population in this study were all employees who worked at PT Tanjung Timberindo Industry as many as 101 employees. The sample in this study was calculated using the slovin formula obatined as many as 50 employees and the sampling technique used was Purposive Sampling. Data analysis and testing consists of validity test, reliability test, descriptive statistics, classical assumption test, multiple regression analysis, partial hypothesis testing (t test), simultaneously (F test), and determination coefficient test. The results of this study indicate that Financial Literacy has a partially significant effect on Interest in Using E-Wallet with a t value of 7,169 > t table 1,667. Perceived Ease of Use has no significant effect partially on Interest in Using E-Wallet with a t value of 0,789 < t table 1,667. Financial Literacy and Perceived Ease of Use have a significant effect simultaneously on Interest in Using E-Wallet with an F Value of 41,404 > F table 2,42 and a coefficient of determinarion of 63,8%.